2015
DOI: 10.1177/1534650115602065
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of a Brief Behavioral Intervention on Food Refusal in a Child With a Fear of Choking

Abstract: This study examined the effects of an exposure-based behavioral treatment on food refusal in a 4-year-old girl who developed a fear of choking after an acute choking episode. Prior to treatment, the child had stopped eating almost all solid foods for 3 months and was primarily consuming a chocolate-flavored pediatric formula. Treatment occurred across the span of 2 weeks and took place at a pediatric feeding program. At the end of treatment, the child accepted over 30 new foods and was no longer dependent on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…One study compared cohorts in their program with and without family involvement [264], and found that weight outcomes did not vary with family involvement, but there was a greater improvement observed in overall symptomatology, and in particular weight concerns and dietary restraint with family involvement. Only three small studies have examined the use of day treatment settings for patients with Avoidant/ Restrictive Food Intake Disorder [278,281,282] and one small study examined this setting for Bulimia Nervosa [279]. One high quality study observed no harm with the addition of a standardized resistance training program to day treatment care as usual for patients with mixed eating disorder diagnoses [283].…”
Section: Level Of Carementioning
confidence: 99%
“…One study compared cohorts in their program with and without family involvement [264], and found that weight outcomes did not vary with family involvement, but there was a greater improvement observed in overall symptomatology, and in particular weight concerns and dietary restraint with family involvement. Only three small studies have examined the use of day treatment settings for patients with Avoidant/ Restrictive Food Intake Disorder [278,281,282] and one small study examined this setting for Bulimia Nervosa [279]. One high quality study observed no harm with the addition of a standardized resistance training program to day treatment care as usual for patients with mixed eating disorder diagnoses [283].…”
Section: Level Of Carementioning
confidence: 99%
“…With acute onset packing not due to skill deficits or lack of experience, the original aetiology may be medical in nature (e.g., gastrointestinal issues; Hagopian et al, 1996; Williams et al, 2011) or a triggering event (e.g., choking episode, allergic reaction, major life changes such as in caregivers or schools; Lenz et al, 2018; Lesser et al, 2022; Seiverling et al, 2016; Tang et al, 2011). However, even once the original aetiology has resolved, packing may persist due to behavioural reasons (e.g., to gain interaction or preferred items or activities, to avoid nonpreferred tasks) (Girolami & Scotti, 2001; González et al, 2014; Piazza et al, 2003; Rivero & Borrero, 2019).…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%
“…In addition, later studies demonstrated continued support for the use of brief behavior-based interventions for fears in this population. For example, one study demonstrated the success of a brief exposure program for treating fear of choking in a young child with ASD (Seiverling et al, 2016). In addition, a book chapter by Davis, Ollendick, and Öst (2012) suggests OST as a potential treatment for specific phobias when comorbid with ASD for several reasons such as the potential for quicker gains in a setting that allows for repeated practice and the potential for real-time parent coaching and involvement.…”
Section: Theoretical and Research Basis For Treatmentmentioning
confidence: 99%